PENGARUH KREDIT PERBANKAN PADA SEKTOR INDUSTRI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO SEKTOR INDUSTRI KALIMANTAN BARAT - B01109077, Wahyu Ramdhani (Jurnal Pembangunan dan Pemerataan, 2014)
The study is titled: "The Effect of Credit in the Industrial Sector Against Gross Domestic Product in the Industry sector of West Kalimantan". The background of this research by means of the support needed to develop and process the results - abundant crops in West Kalimantan. To build the business processing industry would have to have substantial capital, so that the necessary role of the banks in order to meet the needs of the business activities of the industry. The purpose of this study was to determine the effect of the credit in the industrial sector to Gross Domestic Product by Industrial Sector In West Kalimantan, the analysis period of 2004-2012. The data is then processed into quarterly data were further analyzed using simple regression analysis. The result showed that the distribution of bank loans extended to the industrial sector in West Kalimantan to the Gross Domestic Product has a positive and significant relationship, thus increasing bank credit will have a direct impact on the increase in Gross Regional Domestic Product. Test Coefficient of Determination (R ^ 2) shows that the effect of credit in the industrial sector in the province of West Kalimantan is at 63.82%. Keywords: Effect of Credit, Gross Domestic Product and Industrial Sector.